Victim Identification, Framing Heuristic and Stress Effects on the Donation Decision - Nihan TOMRİS KÜÇÜN; Sezen GÜNGÖR (Prizren Social Science Journal)
The tendency of an individual to share his beings with other people arises from the social aspect of human nature. Especially in today's conditions where the gap between advantageous and disadvantaged groups is getting deeper, donation is extremely important to reach a global level of welfare and to create fair living standards for all. Due to the stated priorities, donation behavior has an important place among both religious and moral values. However, the factors that lead an individual towards donation behavior are not only social rules. In addition to external factors, important internal factors such as emotions also play a big role in the donation decision. In addition, there are many variables such as the donated thing itself, total assets of the donor and indeed the characteristics of the donor. Donation behavior, which is widely examined in the literature, is also considered as an important decision making subject.